Enhancement of mechanical properties of tungsten alloy via disordered microstructure and solid solution strengthening. (January 2023) - Mao, Ruipeng; Xiang, Daoping
Graphical abstract: Highlights: A novel W-Ni3 Al-FeSiB alloy with excellent mechanical properties was fabricated. Adding metallic glass powder facilitated the alloy's densification at low sintering temperature. The W and binder phase were simultaneously solid-solution strengthened. Nanaoscale disordered interface and amorphous particle strengthened alloy's mechanical properties. Abstract: Poor mechanical properties and large tungsten grains prevent the reported W-Ni3 Al alloy from being used as a kinetic energy penetrator (KEP). Based on our previous flaky Ni3 Al and in-situ nano-Al2 O3 strengthening in W-Ni3 Al alloy, the solid solution strengthening, disordered interface, and amorphous particle were introduced to further improve its comprehensive properties in this research. The generated solid solutions, such as W(Si, B), (Ni, Fe)3 (Al, Fe, W)-B, and (Ni, Fe, Al, W, B), simultaneously strengthened the W and binder phase. The disordered interface with a width of about 60 nm hindered the crack initiation along its boundary and decreased the driving force of tungsten grain growth. Adding metallic glass powder can not only obtain amorphous FeSiB particles, but also make the relative density of the alloy up to 99.78% ± 0.21%. As a result, the novel prepared W-Ni3 Al-FeSiB alloy exhibited outstanding mechanical properties, with its bending strength and hardness of 1654.50 ± 31.20 MPa and 74.70 ± 0.54 HRA, respectively.